Structural diversification of bioactive bibenzyls through modular co-culture leading to the discovery of a novel neuroprotective agent - Yuyu Liu; Xinnan Li; Songyang Sui; Jingshu Tang; Dawei Chen; Yuying Kang; Kebo Xie; Jimei Liu; Jiaqi Lan; Lei Wu; Ridao Chen; Ying Peng; et al. (Acta Pharmaceutica Sinica B, 2023)
Bibenzyls, a kind of important plant polyphenols, have attracted growing attention for their broad and remarkable pharmacological activities. However, due to the low abundance in nature, uncontrollable and environmentally unfriendly chemical synthesis processes, these compounds are not readily accessible. Herein, one high-yield bibenzyl backbone-producing Escherichia coli strain was constructed by using a highly active and substrate-promiscuous bibenzyl synthase identified from Dendrobium officinale in combination with starter and extender biosynthetic enzymes. Three types of efficiently post-modifying modular strains were engineered by employing methyltransferases, prenyltransferase, and glycosyltransferase with high activity and substrate tolerance together with their corresponding donor biosynthetic modules. Structurally different bibenzyl derivatives were tandemly and/or divergently synthesized by co-culture engineering in various combination modes. Especially, a prenylated bibenzyl derivative (12) was found to be an antioxidant that exhibited potent neuroprotective activity in the cellular and rat models of ischemia stroke. RNA-seq, quantitative RT-PCR, and Western-blot analysis demonstrated that 12 could up-regulate the expression level of an apoptosis-inducing factor, mitochondria associated 3 (Aifm3), suggesting that Aifm3 might be a new target in ischemic stroke therapy. This study provides a flexible plug-and-play strategy for the easy-to-implement synthesis of structurally diverse bibenzyls through a modular co-culture engineering pipeline for drug discovery.